Immune activation by microbiome shapes the colon mucosa: Comparison between healthy rat mucosa under conventional and germ-free conditions - Čaja, Fabián; Stakheev, Dmitry; Chernyavskiy, Oleksander; Křížan, Jiří; Dvořák, Jiří; Rossmann, Pavel; Štěpánková, Renata; Makovický, Peter; Makovický, Pavol; Kozáková, Hana; Vannucci, Luca (Journal of immunotoxicology, 2021)
Germ-free animals (GF) are those without a microbiome since birth. This particular biological model has become one of special interest with the growing evidence of importance of the microbiome in the life, development, adaptation, and immunity of humans and animals in the environments in which they live. Anatomical differences observed in GF compared with conventionally-reared animals (CV) has given rise to the question of the influence of commensal microflora on the development of structure and function (even immunological) of the bowel. Only recently, thanks to achievements in microscopy and associated methods, structural differences can be better evaluated and put in perspective with the immunological characteristics of GF vs. CV animals. This study, using a GF rat model, describes for the first time the possible influence that the presence of commensal microflora, continuously stimulating mucosal immunity, has on the collagen scaffold organization of the colon mucosa. Significant differences were found between CV and GF mucosa structure with higher complexity in the CV rats associated to a more activated immune environment. The immunological data suggest that, in response to the presence of a microbiome, an effective homeostatic regulation in developed by the CV rats in healthy conditions to avoid inflammation and maintain cytokine levels near the spontaneous production found in the GF animals. The results indicated that collagen scaffold adapted to the immune microenvironment; therefore, it is apparent that the microbiome was able to condition the structure of the colon mucosa.
Keywords: collagen; stroma; Germ-Free Life; microbiome; střevní sliznice; colon mucosa; Immunity, Mucosal; zvířata; Rats; Colon; Germ-free animals; mucosal immunity; kolon; mikrobiota; gnotobiologické modely; slizniční imunita; krysa rodu Rattus; Animals; Intestinal Mucosa; Microbiota